Longitudinal Assessment of Ellipsoid Zone Mapping Parameters in Retinal Venous Occlusive Disease With Associated Macular Edema. (January 2021) - Abraham, Joseph R.; Boss, Joseph; Babiuch, Amy S.; Singh, Rishi P.; Srivastava, Sunil; Reese, Jamie; Ehlers, Justis P.
Purpose: This work evaluated the longitudinal dynamics of ellipsoid zone (EZ) integrity in retinal vein occlusion (RVO) with macular edema and their relation to outcomes. Methods: Clinical characteristics and optical coherence tomography data of patients with RVO and associated macular edema were collected at baseline and at 3 and 12 months. Macular cube scans were exported into EZ and retinal-layer analysis software. Longitudinal EZ parameters and visual acuity (VA) outcomes were regressed and correlated. Results: The study included 108 eyes of 108 patients; all eyes were treated with antivascular endothelial growth factor therapy at the baseline visit. VA improved from 20/97 at baseline to 20/52 at 3 months and 12 months ( P  < .001), correlating with EZ integrity at each time point ( P  < .001). At 12 months following initiation of antivascular endothelial growth factor therapy, EZ partial attenuation and EZ total attenuation improved over 12 months from 16.4% to 8.5% ( P  < .001) and from 12.3% to 5.9% ( P  < .001), respectively. VA improvement from baseline to 12 months correlated with improvement of EZ partial and total attenuation ( P  < .001). Baseline EZ characteristics did not predict VA outcomes, but at 3 months, EZ parameters did predict improvement in visual outcomes by 12 months ( P  < .01). Conclusions: EZ and outer retinal integrity are correlated with functional outcomes in RVO. Following treatment, EZ integrity improves and is associated with functional improvement. In RVO baseline, EZ features were not associated with 1-year VA outcomes, but evaluation of EZ integrity at 3 months was linked to 1-year outcomes.